Economic Contributions of Agriculture, Natural Resources, and Related Food Industries in Florida in 2011 - Alan W. Hodges; Mohammad Rahmani; Thomas J. Stevens (EDIS)
Agriculture, natural resources, and related food industries remain a significant force in the economy of Florida, and it is important to recognize their economic contributions for informed public policy. We evaluated the economic contributions of these industries for calendar year 2011 to update previous reports and provide further information on economic trends in the wake of the historic global recession of 2007–2009. This 40-page report was written by Alan W. Hodges, Mohammad Rahmani, and Thomas J. Stevens, and published by the UF Department of Food and Resource Economics, June 2013.